A BREATH OF NEW NARRATIVES OF ACTIONS IN PUBLIC SCHOOLS: FROM TEACHING TO PEDAGOGY - Marcelino, Bernardete de Lourdes Alvares; da Silva, Maurício Pedro (Seven Editora, 2025)
This article aims to engage with the history of teaching and Pedagogy programs, with a critical analysis of initial training as a precursor to teacher identity construction. It discusses narratives grounded in research by Bernadete Gatti, Imbernón, Franco, and Paulo Freire, with the aim of reflecting on the profession of teaching in Brazil.DOI: https://doi.org/10.56238/sevened2025.030-077